Bone health in patients undergoing surgery for primary hyperparathyroidism at Tygerberg Hospital, Cape Town, South Africa. Issue 1 (2nd January 2021) - Budge, M; Conradie, W; Beviss-Challinor, K; Martin, L; Conradie, M; Coetzee, A
Abstract : Background: Increased bone resorption is a well-described consequence of primary hyperparathyroidism (PHPT). In South Africa, little is known about the impact of PHPT on skeletal health. Objective: To determine the prevalence of decreased bone mineral density (BMD), vertebral fractures and osteitis fibrosa cystica in patients with PHPT who underwent parathyroidectomy. Methods: Retrospective study of patients who underwent parathyroidectomy for PHPT at Tygerberg Hospital in Cape Town, from January 2010 to December 2019. Clinical, biochemical and BMD parameters are described. Results: Final analysis included 56 patients (median age 63.5 years; 80.4% female). Initial calcium, parathyroid hormone (PTH) and 25-hydroxyvitamin D (25[OH]D) levels were 2.93 mmol/l, 19.4 pmol/l and 34.0 nmol/l, respectively. Of the total cohort, 71.4% had decreased BMD. The prevalence of osteoporosis and osteopenia in postmenopausal women and men ≥ 50 years was 50.0% and 39.1% respectively; low bone mass for age in premenopausal women and men < 50 years was 20.0%. Vertebral fractures were seen in 21.2% of patients on radiography. Osteitis fibrosa cystica was present in five patients (9.6%). PTH levels were significantly elevated in patients with osteoporosis compared with those with normal BMD (36.4 vs. 16.1 pmol/l; p  = 0.02). Conclusion: Two-thirds of patients who underwent parathyroidectomy for PHPT had decreased BMD, with osteoporosis present in 50% of postmenopausal women and older men. One in five had vertebral fractures. These findings underscore the importance of skeletal assessment in the management of PHPT.